2016
DOI: 10.5603/kp.a2015.0100
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of myocardial perfusion single-photon emission computed tomography with attenuation correction

Abstract: A b s t r a c tBackground: Myocardial perfusion single-photon emission computed tomography (SPECT) is one of the basic tools used for the purpose of diagnosis of coronary artery disease (CAD), prognosis of its unfavourable consequences, and evaluation of therapy effectiveness. However, its efficacy is compromised by a relatively low specificity of detection of perfusion defects, which is attributed to attenuation of gamma rays inside the patient's body, causing artefacts erroneously taken for perfusion defects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…As the current study demonstrated, the vascular area that most benefited from attenuation correction was RCA. Similar to the literature, attenuation correction yielded a decrease in the sensitivity in the whole group, while the specificity increased in the whole group and male subgroup ( 6 ).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…As the current study demonstrated, the vascular area that most benefited from attenuation correction was RCA. Similar to the literature, attenuation correction yielded a decrease in the sensitivity in the whole group, while the specificity increased in the whole group and male subgroup ( 6 ).…”
Section: Discussionsupporting
confidence: 84%
“…There are also papers that have reported that attenuation correction increases the capacitance of the detection of LAD disease ( 26 ). In contrast to Wolak et al ( 27 ), AC imaging has also been reported to be useful in female patients ( 6 ). Additionally, some publications have argued that apical defects observed in AC images may be secondary to true apical thinning ( 28 ).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations